2021
DOI: 10.1016/j.sigpro.2021.108090
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Epanechnikov mixture regression in image coding

Abstract: Kernel methods have been studied extensively in recent years. We propose a three-dimensional (3-D) Epanechnikov Mixture Regression (EMR) based on our Epanechnikov Kernel (EK) and realize a complete framework for image coding. In our research, we deduce the covariance-matrix form of 3-D Epanechnikov kernels and their correlated statistics to obtain the Epanechnikov mixture models. To apply our theories to image coding, we propose the 3-D EMR which can better model an image in smaller blocks compared with the co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The experimental results showed that the discontinuity made the EK an energy-concentrated function and produced efficient results compared with a Gaussian kernel. Subsequently, in [18], we proposed a coding framework using 3-D Epanechnikov mixture regression (EMR) and Gaussian mixture regression (GMR) that could outperform JPEG image compression. Different from our previous papers, the study in this study aims to show that the EI-correlation of an LF image can be utilized for compression.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that the discontinuity made the EK an energy-concentrated function and produced efficient results compared with a Gaussian kernel. Subsequently, in [18], we proposed a coding framework using 3-D Epanechnikov mixture regression (EMR) and Gaussian mixture regression (GMR) that could outperform JPEG image compression. Different from our previous papers, the study in this study aims to show that the EI-correlation of an LF image can be utilized for compression.…”
Section: Introductionmentioning
confidence: 99%